FINDING A UNIVERSAL AND CULTURAL CARE - Rohrbach, Cecilia (Investigación y Educación en Enfermería, 2008)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Every one hold analytical responsibility when a caring theory is shown be cause building and conﬁrming or invalidating postulates contributes to the progress of science Criticism, in its original analysis sense, it is part of science as well as conﬁrming and enriching legitimately its khowledge and application. Transcultural care formed and mainly transmitted by American nurses, it is originated within American anthropology. It is convenient to reﬂect, in order to elude privileging speciﬁc cultural group’s studies, impoverishing those groups of a western culture. This speciﬁc situation encourages analyzing some aspects of the American anthropology with a European perspective attaching those positions and proposing a universal and cultural care.